Diversos escenarios de las emociones del grupo IRA - Gajos, Aleksandra (Neophilologica, 2012)
The aim of this paper is to present various scenarios of the emotion of ANGE R in Spanish and Polish languages based on the English language. We can observe that the differences between the prototypical English scenario and the Spanish-Polish one (viz lack of the control stage / losing control) come from the differences in the conceptualization and view of the world. The above mentioned cultural differences cause the need to conceptualize and create different lexemes such as indignación / furor / enojo y la irritación. In the English language we deal with a single lexeme, ANGE R, which corresponds to two different lexemes in Spanish and Polish: ira / gniew and rage / złość. This distinction must be taken into account when we talk about the prototypical scenario of the emotions of the IRA group which in general appears to have more typical features of rabia / złość that ira / gniew, although it is the latter which gives the name to the whole group of universal emotions of IRA / GNIEW .